Związek między zachowaniami żywieniowymi a występowaniem otyłości u młodzieży ponadgimnazjalnej Zespołu Szkół Chemicznych w Bydgoszczy. Zachowania żywieniowe i otyłość u młodzieży ponadgimnazjalnej - Pluta, Agnieszka; Jaczek-Kierzenkowska, Jolanta; Faleńczyk, Kamila; Budnik-Szymoniuk, Maria; Basińska-Drozd, Halina (Journal of Education, Health and Sport, 2015)
Pluta Agnieszka, Jaczek-Kierzenkowska Jolanta, Faleńczyk Kamila, Budnik‑Szymoniuk Maria, Basińska-Drozd Halina. Związek między zachowaniami żywieniowymi a występowaniem otyłości u młodzieży ponadgimnazjalnej Zespołu Szkół Chemicznych w Bydgoszczy. Zachowania żywieniowe i otyłość u młodzieży ponadgimnazjalnej = The relationship between dietary behavior and obesity at the high school youth team Chemical Schools in Bydgoszcz. Eating behavior and obesity in high school youth. Journal of Education, Health and Sport. 2015;5(5):435-444. ISSN 2391-8306. DOI 10.5281/zenodo.18060 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A435-444 https://pbn.nauka.gov.pl/works/562263 http://dx.doi.org/10.5281/zenodo.18060 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2015. Revised 18.04.2015. Accepted: 24.05.2015. Związek między zachowaniami żywieniowymi a występowaniem otyłości u młodzieży ponadgimnazjalnej Zespołu Szkół Chemicznych w Bydgoszczy. Zachowania żywieniowe i otyłość u młodzieży ponadgimnazjalnej The relationship between dietary behavior and obesity at the high school youth team Chemical Schools in Bydgoszcz. Eating behavior and obesity in high school youth Agnieszka Pluta1, Jolanta Jaczek-Kierzenkowska2, Kamila Faleńczyk1, Maria Budnik‑Szymoniuk1, Halina Basińska-Drozd1 1Zakład Pielęgniarstwa Społecznego, Wydział Nauk o Zdrowiu Uniwersytetu Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy 2WOZ "GRYF-MED" w Bydgoszczy Adres do korespondencji / Address for correspondence dr n. o zdrowiu Agnieszka Pluta Zakład Pielęgniarstwa Społecznego, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu ul. Łukasiewicza 1, Bydgoszcz 85-801 e-mail: agnieszkapluta@poczta.onet.pl Streszczenie Wprowadzenie. Pozytywne zachowania żywieniowe warunkują zdrowy styl życia dzieci i młodzieży. Nieprawidłowe zachowania żywieniowe są przyczyną wielu zaburzeń i chorób zarówno w wieku szkolnym jak i dorosłym. Wśród najczęściej występujących zaburzeń jest otyłość, która warunkuje szereg innych schorzeń jak na przykład cukrzyca, choroby układu sercowo-naczyniowego, osteoporoza czy wady postawy. Dzieciństwo jest okresem najwłaściwszym na ukształtowanie pozytywnych zachowań. Materiał i metoda. Badaniami objęto liczbę 100 uczniów klas maturalnych Zespołu Szkół Chemicznych w Bydgoszczy. W pracy jako narzędzie badawcze wykorzystano kwestionariusz ankiety własnego autorstwa oraz analizę formularzy sprawozdawczych z przeprowadzonych badań przesiewowych i profilaktycznych badań lekarskich. Cel. Celem niniejszej pracy była analiza zachowań żywieniowych i ich wpływ na występowanie otyłości u młodzieży ponadgimnazjalnej. Wyniki. Młodzież płci męskiej stanowiła większość w badanej grupie – 54 osoby (54,0%). Większość uczniów, to osoby o wartości prawidłowej wskaźnika BMI – 51,0%. Poniżej tej wartości odnotowano 9,0% uczniów, powyżej 40,0% uczniów, z czego większość to osoby z nadwagą – 35,0%. Średnia wartość wskaźnika BMI u mężczyzn była istotnie statystycznie wyższa niż u kobiet 24,80±3,49 vs 22,82±3,88; p<0,05. Co piąty uczeń nie spożywał śniadania przed wyjściem do szkoły nigdy – 20,0%. Połowa ankietowanych zabierała codziennie do szkoły II śniadanie. Większość uczniów spożywało 4-5 posiłków dziennie – 72,0%. Co dwudziesty uczeń zjadał mniej niż 3 posiłki dziennie – 5,0%. Wśród ogółu badanych 46 % nie spożywało dziennie 5 porcji owoców i warzyw. Wnioski. Liczba uczniów z nadwagą i otyłością wzrasta. Nieznacznie wyższy poziom zachowań prozdrowotnych prezentowały kobiety (uczennice). Zdecydowana większość respondentów uważała, że odżywia się prawidłowo. Prawidłowy styl odżywiania częściej prezentowali badani płci żeńskiej, a prawidłową wartość BMI mieszkańcy miasta. Słowa kluczowe: zachowania żywieniowe, otyłość, młodzież. Summary Introduction. Positive eating habits healthy lifestyle condition of children and youth. Improper eating habits are the cause of many disorders and diseases of both schoolchildren and adults. Among the most common disorder is obesity, which determines a number of other conditions such as diabetes, cardiovascular diseases, osteoporosis and posture. Childhood is a time most appropriate for shaping positive behaviors. Material and methods. The study included the number of 100 students in grades Baccalaureate School Complex Chemical in Bydgoszcz. The study was used as a research tool questionnaire and the analysis of their own by reporting forms from the study screening and preventive medical examinations. The aim of this study was to analyze eating behaviors and their impact on the incidence of obesity among high school youth. Results. Youth accounted for the majority of male in the group - 54 people (54.0%). Most of the students are people with the correct value of BMI - 51.0%. Below this value was reported by 9.0% of students, over 40.0% of students, most of whom are overweight - 35.0%. The average BMI in men was significantly higher than in women 24,80±3,49 vs 22,82±3,88; p <0.05. Every fifth student does not eat breakfast before going to school ever - 20.0%. Half of the respondents lifted to school every day was taking a snack. Most of the students consumed 4-5 meals a day - 72.0%. Every twentieth student ate less than 3 meals a day - 5.0%. Among all respondents 46% did not eat 5 servings a day of fruits and vegetables. Conclusions. The number of students who are overweight or obese increases. Slightly higher level of health behaviors presented women (students). The vast majority of respondents believed that nourishes properly. Proper eating habits often presented female subjects and normal BMI residents of the city. Key words: feeding behavior, obesity, youth.